Security intelligence a practitioner's guide to solving enterprise security challenges - Li, Qing 1971-; Clark, Gregory (Wiley, 2015)
Identify, deploy, and secure your enterprise Security Intelligence, A Practitioner's Guide to Solving Enterprise Security Challenges is a handbook for security in modern times, against modern adversaries. As leaders in the design and creation of security products that are deployed globally across a range of industries and market sectors, authors Qing Li and Gregory Clark deliver unparalleled insight into the development of comprehensive and focused enterprise security solutions. They walk you through the process of translating your security goals into specific security technology domains, fo.
Includes bibliographical references and index. - Online resource; title from PDF title page (Ebsco, viewed April 13, 2015)
Keywords: Electronic information resources -- Access control; Computer networks -- Security measures; Computer security; Sources d'information électroniques; Accès; Contrôle; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures; Electronic information resources; Access control; Computers and IT